Interferon gamma upregulates the cytokine receptors IFNGR1 and TNFRSF1A in HT-29-MTX E12 cells. (August 2022) - Johnson, Brandon; Panek, Paulina; Yu, Andy; Fischer, Elizabeth; Koba, Marli; Mendoza Hermosillo, Daniel; Capaldo, Christopher T.
Abstract: The intestinal mucosa protects the body from physical damage, pathogens, and antigens. However, inflammatory bowel diseases (IBDs) patients suffer from poor mucosal tissue function, including the lack of an effective cellular and/or mucus barrier. We investigated the mucus producing human colonic epithelial cell line HT29-MTX E12 to study its suitability as an in vitro model of cell/mucus barrier adaption during IBD. It was found that the proinflammatory cytokine interferon-gamma (IFN-γ), but not tumor necrosis factor-alpha (TNF-α), reduced cell viability. IFN-γ and TNF-α were found to synergize to decrease barrier function, as measured by trans -epithelial electric resistance (TER) and molecular flux assays. Cells cultured under an air-liquid interface produced an adherent mucus layer, and under these conditions reduced barrier function was found after cytokine exposure. Furthermore, IFN-γ, but not TNF-α treatment, upregulated the IFN-γ receptor 1 (IFNGR1) and TNF-α receptor super family 1A (TNFRSF1A) subunit mRNA in vitro . Co-stimulation resulted in increased mRNA expression of CLDN 2 and 5, two gene known to play a role in epithelial barrier integrity. Analysis of IBD patient samples revealed IFNGR1 and TNFRSF mRNA increased coincidently with guanylate binding protein 1 (GBP1) expression, an indicator of NFkB activity. Lastly, CLDN2 was found at higher levels in IBD patients while HNF4a was suppressed with disease. In conclusion, IFN-γ and TNF-α degrade epithelial/mucus barriers coincident with changes in CLDN gene and cytokine receptor subunit mRNA expression in HT29-MTX E12 cells. These changes largely reflect those observed in IBD patient samples.